2016
DOI: 10.1186/s10194-016-0599-8
|View full text |Cite
|
Sign up to set email alerts
|

Interictal burden attributable to episodic headache: findings from the Eurolight project

Abstract: BackgroundMost primary headaches are episodic, and most estimates of the heavy disability burden attributed to headache derive from epidemiological data focused on the episodic subtypes of migraine and tension-type headache (TTH). These disorders give rise directly but intermittently to symptom burden. Nevertheless, people with these disorders may not be symptom-free between attacks. We analysed the Eurolight dataset for interictal burden.MethodsEurolight was a cross-sectional survey using modified cluster sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
108
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(115 citation statements)
references
References 23 publications
4
108
2
Order By: Relevance
“…For example, GBD currently considers only the disability burden associated with the ictal state of headache disorders, despite evidence of interictal burden in a considerable proportion of people with migraine . Whereas the ictal burden is typically present during only a few days in every month, interictal burden can make itself felt on all of the other days, thereby considerably affecting patients’ daily activities . A study in a European population found that time in the interictal state, when symptoms might be present continuously, was, on average, 317 days/year for sufferers of migraine …”
Section: Epidemiologymentioning
confidence: 99%
“…For example, GBD currently considers only the disability burden associated with the ictal state of headache disorders, despite evidence of interictal burden in a considerable proportion of people with migraine . Whereas the ictal burden is typically present during only a few days in every month, interictal burden can make itself felt on all of the other days, thereby considerably affecting patients’ daily activities . A study in a European population found that time in the interictal state, when symptoms might be present continuously, was, on average, 317 days/year for sufferers of migraine …”
Section: Epidemiologymentioning
confidence: 99%
“…Further, the notion that migraine is a disease preferentially affecting rich industrialised nations is dispelled by the comparison in Table 2 between low- and high-income countries. It is worth adding here that GBD currently considers only the disability burden associated with the ictal state of headache disorders, whereas there is evidence of interictal burden in a considerable proportion of people with migraine and in a small proportion of people with TTH [20]. The significance of interictal burden is that, although it may be at relatively low level, it is present for longer periods of time than ictal burden.…”
Section: How Much Headache Is There In the World?mentioning
confidence: 99%
“…The significance of interictal burden is that, although it may be at relatively low level, it is present for longer periods of time than ictal burden. With new data indicating that interictal disability in headache disorders is real and measurable [20], future iterations of GBD should consider adding this component of disability.…”
Section: How Much Headache Is There In the World?mentioning
confidence: 99%
“…It is now ranked as the third cause of years lived with disability in people aged 15‐50 years old . The frequency and severity of attacks influence the burden, but the interictal symptoms and cephalalgiaphobia are now recognized as an important part of the disability load . The locus of control and feeling of self‐efficacy influence the quality of life in pain disorders and also migraine …”
mentioning
confidence: 99%